Low-carbon City and New-type Urbanization: Proceedings of Chinese Low-carbon City Development International Conference - Feng, S (Springer, 2015)
In the face of increasingly serious resource and environmental challenges, the world has already accepted low-carbon development as the main way forward for future city construction. Chinese cities have encountered many problems during their development, including land constraints, energy shortages, traffic congestion and air pollution. For this reason, the national meeting of the Central Work Conference on Urbanization made the strategic decision to take a new approach to urbanization and indicated that in future the key features of urbanization in China will be low-carbon development and harmony between the environment and resources. This book discusses the "low-carbon city" as the new pattern of Chinese urbanization. This represents a major change and takes "intensive land use,” “intelligent,” “green” and “low carbon" as its key words. Low carbon will become an important future development direction for Chinese urbanization development.